Studi Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening serta Budaya Organisasi dan Employee Engagement sebagai Prediktor di Destinasi Pariwisata Kopi Luwak Mataram Group Yogyakarta - Hasbi, Sirajudin; Supriyadi, Andhi; Hendrajaya, Hendrajaya (Mahesa Research Center, 2025)
Culinary tourism is becoming more and more popular around the world. Many travelers enjoy trying traditional foods and drinks from different regions as part of their journeys. This study looks into how 1) the company's culture and how much employees feel involved at work affect how satisfied they are with their jobs; 2) the company's culture, employee involvement, and job satisfaction affect how productive employees are at work; and 3) the company's culture and employee involvement affect how well employees perform, with job satisfaction acting as a middle factor. The study used numbers and data to find answers. It included 94 employees from the Kopi Luwak Mataram Group in Yogyakarta. Information was gathered through questionnaires given to the workers. The data was analyzed using SPSS, and tests were done to make sure the questions were good and consistent. Based on the results, the study found that 1) the company's culture and employee involvement do affect job satisfaction at Kopi Luwak Mataram Group. 2) The company's culture, employee involvement, and job satisfaction all have an effect on work productivity at the same company. 3) The company's culture and employee involvement influence employee performance, with job satisfaction playing a key role in this connection.